Appearance of the single gyroid network phase in "nuclear pasta" matter - Schuetrumpf, Bastian; Klatt, Michael; Iida, K.; Schröder-Turk, Gerd; Maruhn, J. A.; Mecke, Klaus; Reinhard, Paul-Gerhard (Physical Review C - Nuclear Physics, 2015)
Nuclear matter under the conditions of a supernova explosion unfolds into a rich variety of spatially structured phases, called nuclear pasta. We investigate the role of periodic networklike structures with negatively curved interfaces in nuclear pasta structures, by static and dynamic Hartree-Fock simulations in periodic lattices. As the most prominent result, we identify for the first time the single gyroid network structure of cubic chiral I4(1)23 symmetry, a well-known configuration in nanostructured soft-matter systems, both as a dynamical state and as a cooled static solution. Single gyroid structures form spontaneously in the course of the dynamical simulations. Most of them are isomeric states. The very small energy differences from the ground state indicate its relevance for structures in nuclear pasta.

Butterfly gyroid nanostructures as a time-frozen glimpse of intracellular membrane development. - Wilts, Bodo D.; Apeleo Zubiri, Benjamin; Klatt, Michael A.; Butz, Benjamin; Fischer, Michael G.; Kelly, Stephen T.; Spiecker, Erdmann; Steiner, Ullrich; Schroeder-Turk, Gerd E. (Science Advances, 2017)
The formation of the biophotonic gyroid material in butterfly wing scales is an exceptional feat of evolutionary engineering of functional nanostructures. It is hypothesized that this nanostructure forms by chitin polymerization inside a convoluted membrane of corresponding shape in the endoplasmic reticulum. However, this dynamic formation process, including whether membrane folding and chitin expression are simultaneous or sequential processes, cannot yet be elucidated by in vivo imaging. We report an unusual hierarchical ultrastructure in the butterfly Thecla opisena that, as a solid material, allows high-resolution three-dimensional microscopy. Rather than the conventional polycrystalline space-filling arrangement, a gyroid occurs in isolated facetted crystallites with a pronounced size gradient. When interpreted as a sequence of time-frozen snapshots of the morphogenesis, this arrangement provides insight into the formation mechanisms of the nanoporous gyroid material as well as of the intracellular organelle membrane that acts as the templat

Characterization of anisotropic Gaussian random fields by Minkowski tensors - Klatt, Michael; Hörmann, Max; Mecke, Klaus (Journal of Statistical Mechanics-Theory and Experiment, 2022)
Gaussian random fields are among the most important models of amorphous spatial structures and appear across length scales in a variety of physical, biological, and geological applications, from composite materials to geospatial data. Anisotropy in such systems can be sensitively and comprehensively characterized by the so-called Minkowski tensors (MTs) from integral geometry. Here, we analytically calculate expected MTs of arbitrary rank for the level sets of Gaussian random fields. The explicit expressions for interfacial MTs are confirmed in detailed simulations. We demonstrate how the MTs detect and characterize the anisotropy of the level sets, and we clarify which shape information is contained in the MTs of different rank. Using an irreducible representation of the MTs in the Euclidean plane, we show that higher-rank tensors indeed contain additional anisotropy information compared to a rank two tensor. Surprisingly, we can nevertheless predict this information from the second-rank tensor if we assume that the random field is Gaussian. This relation between tensors of different rank is independent of the details of the model. It is, therefore, useful for a null hypothesis test that detects non-Gaussianities in anisotropic random fields.
CRIS-Team WoS Importer:2022-05-06

Critical pore radius and transport properties of disordered hard- And overlapping-sphere models - Klatt, Michael; Ziff, Robert M.; Torquato, Salvatore (Physical Review E, 2021)
Transport properties of porous media are intimately linked to their pore-space microstructures. We quantify geometrical and topological descriptors of the pore space of certain disordered and ordered distributions of spheres, including pore-size functions and the critical pore radius . We focus on models of porous media derived from maximally random jammed sphere packings, overlapping spheres, equilibrium hard spheres, quantizer sphere packings, and crystalline sphere packings. For precise estimates of the percolation thresholds, we use a strict relation of the void percolation around sphere configurations to weighted bond percolation on the corresponding Voronoi networks. We use the Newman-Ziff algorithm to determine the percolation threshold using universal properties of the cluster size distribution. The critical pore radius is often used as the key characteristic length scale that determines the fluid permeability . A recent study suggested for porous media with a well-connected pore space an alternative estimate of based on the second moment of the pore size , which is easier to determine than . Here, we compare to the second moment of the pore size , and indeed confirm that, for all porosities and all models considered, is to a good approximation proportional to . However, unlike , the permeability estimate based on does not predict the correct ranking of for our models. Thus, we confirm to be a promising candidate for convenient and reliable estimates of the fluid permeability for porous media with a well-connected pore space. Moreover, we compare the fluid permeability of our models with varying degrees of order, as measured by the order metric. We find that (effectively) hyperuniform models tend to have lower values of than their nonhyperuniform counterparts. Our findings could facilitate the design of porous media with desirable transport properties via targeted pore statistics.
CRIS-Team Scopus Importer:2021-07-30

Detecting structured sources in noisy images via Minkowski maps - Klatt, Michael A.; Mecke, Klaus (EPL - Europhysics Letters, 2019)
Astronomy, biophysics, and material science often depend on the possibility to extract information out of faint spatial signals. Here we present a morphometric analysis technique to quantify the shape of structural deviations in greyscale images. It identifies important features in noisy spatial data, especially for short observation times and low statistics. Without assuming any prior knowledge about potential sources, the additional shape information can increase the sensitivity by 14 orders of magnitude compared to previous methods. Rejection rates can increase by an order of magnitude. As a key ingredient to such a dramatic increase, we accurately describe the distribution of the homogeneous background noise in terms of the density of states Omega(A, P, chi) for the area A, perimeter P, and Euler characteristic. of random black-and-white images. The technique is successfully applied to data of the H.E.S.S. experiment for the detection of faint extended sources. Copyright (C) EPLA, 2020
CRIS-Team WoS Importer:2020-05-08

Direct relations between morphology and transport in Boolean models - Scholz, Christian; Klatt, Michael; Mecke, Klaus; Wirner, Frank; Hirneise, Daniel; Schröder-Turk, Gerd; Bechinger, Clemens (Physical Review E, 2015)
We study the relation of permeability and morphology for porous structures composed of randomly placed overlapping circular or elliptical grains, so-called Boolean models. Microfluidic experiments and lattice Boltzmann simulations allowus to evaluate a power-lawrelation between theEuler characteristic of the conducting phase and its permeability. Moreover, this relation is so far only directly applicable to structures composed of overlapping grains where the grain density is known a priori. We develop a generalization to arbitrary structures modeled by Boolean models and characterized by Minkowski functionals. This generalization works well for the permeability of the void phase in systems with overlapping grains, but systematic deviations are found if the grain phase is transporting the fluid. In the latter case our analysis reveals a significant dependence on the spatial discretization of the porous structure, in particular the occurrence of single isolated pixels. To link the results to percolation theory we performed Monte Carlo simulations of the Euler characteristic of the open cluster, which reveals different regimes of applicability for our permeability-morphology relations close to and far away from the percolation threshold.

Exotic cluster structures in the mean-field theory - Klatt, Michael; Ichikawa, T.; Iida, K.; Itagaki, N.; Maruhn, J. A.; Matsuyanagi, K.; Mecke, Klaus; Ohkubo, S.; Reinhard, Paul-Gerhard; Schuetrumpf, B. (Journal of Physics: Conference Series, 2013)
Investigations of exotic cluster-like phenomena in the framework of the Skyrme-Hartree-Fock approach are reported. The occurrence of highly excited isomeric states is discussed in connection with the question of their stability in static and time-dependent Hartree Fock (TDHF) calculations. We find rotational stabilization of a 4α chain structure in 16O occurring for a limited range of angular momenta. A toroidal configuration of 40Ca was also stabilized by rotation and provides a very interesting example of rotation about a symmetry axis with a strictly quantized total angular momentum. Finally we look at the formation of nuclear pasta phases in a time-dependent approach and their classification.
CRIS-Team Scopus Importer:2023-07-24

Gap Sensitivity Reveals Universal Behaviors in Optimized Photonic Crystal and Disordered Networks - Klatt, Michael; Steinhardt, Paul J.; Torquato, Salvatore (Physical Review Letters, 2021)
Through an extensive series of high-precision numerical computations of the optimal complete photonic band gap (PBG) as a function of dielectric contrast for a variety of crystal and disordered heterostructures, we reveal striking universal behaviors of the gap sensitivity , the first derivative of the optimal gap-to-midgap ratio . In particular, for all our crystal networks, takes a universal form that is well approximated by the analytic formula for a 1D quarter-wave stack, . Even more surprisingly, the values of for our disordered networks converge to for sufficiently large . A deeper understanding of the simplicity of this universal behavior may provide fundamental insights about PBG formation and guidance in the design of novel photonic heterostructures.
CRIS-Team Scopus Importer:2021-07-30

Local Number Fluctuations in Hyperuniform and Nonhyperuniform Systems: Higher-Order Moments and Distribution Functions - Torquato, Salvatore; Kim, Jaeuk; Klatt, Michael A. (Physical Review X, 2021)
The local number variance σ2(R) associated with a spherical sampling window of radius R enables a classification of many-particle systems in d-dimensional Euclidean space Rd according to the degree to which large-scale density fluctuations are suppressed, resulting in a demarcation between hyperuniform and nonhyperuniform phyla. To more completely characterize density fluctuations, we carry out an extensive study of higher-order moments or cumulants, including the skewness γ1(R), excess kurtosis γ2(R), and the corresponding probability distribution function P[N(R)] of a large family of models across the first three space dimensions, including both hyperuniform and nonhyperuniform systems with varying degrees of short- and long-range order. To carry out this comprehensive program, we derive new theoretical results that apply to general point processes, and we conduct high-precision numerical studies. Specifically, we derive explicit closed-form integral expressions for γ1(R) and γ2(R) that encode structural information up to three-body and four-body correlation functions, respectively. We also derive rigorous bounds on γ1(R), γ2(R), and P[N(R)] for general point processes and corresponding exact results for general packings of identical spheres. High-quality simulation data for γ1(R), γ2(R), and P[N(R)] are generated for each model. We also ascertain the proximity of P[N(R)] to the normal distribution via a novel Gaussian "distance"metric l2(R). Among all models, the convergence to a central limit theorem (CLT) is generally fastest for the disordered hyperuniform processes in two or higher dimensions such that γ1(R)∼l2(R)∼R-(d+1)/2 and γ2(R)∼R-(d+1) for large R. The convergence to a CLT is slower for standard nonhyperuniform models and slowest for the "antihyperuniform"model studied here. We prove that one-dimensional hyperuniform systems of class I or any d-dimensional lattice cannot obey a CLT. Remarkably, we discover a type of universality in that, for all of our models that obey a CLT, the gamma distribution provides a good approximation to P[N(R)] across all dimensions for intermediate to large values of R, enabling us to estimate the large-R scalings of γ1(R), γ2(R), and l2(R). For any d-dimensional model that "decorrelates"or "correlates"with d, we elucidate why P[N(R)] increasingly moves toward or away from Gaussian-like behavior, respectively. Our work sheds light on the fundamental importance of higher-order structural information to fully characterize density fluctuations in many-body systems across length scales and dimensions, and thus has broad implications for condensed matter physics, engineering, mathematics, and biology.
CRIS-Team Scopus Importer:2021-06-04

Low-temperature statistical mechanics of the Quantizer problem: Fast quenching and equilibrium cooling of the three-dimensional Voronoi liquid - Hain, Tobias M.; Klatt, Michael A.; Schroder-Turk, Gerd E. (Journal of Chemical Physics, 2020)
The quantizer problem is a tessellation optimization problem where point configurations are identified such that the Voronoi cells minimize the second moment of the volume distribution. While the ground state (optimal state) in 3D is almost certainly the body-centered cubic lattice, disordered and effectively hyperuniform states with energies very close to the ground state exist that result as stable states in an evolution through the geometric Lloyd's algorithm [M. A. Klatt et al. Nat. Commun. 10, 811 (2019)]. When considered as a statistical mechanics problem at finite temperature, the same system has been termed the "Voronoi liquid" by Ruscher, Baschnagel, and Farago [Europhys. Lett. 112, 66003 (2015)]. Here, we investigate the cooling behavior of the Voronoi liquid with a particular view to the stability of the effectively hyperuniform disordered state. As a confirmation of the results by Ruscher et al., we observe, by both molecular dynamics and Monte Carlo simulations, that upon slow quasi-static equilibrium cooling, the Voronoi liquid crystallizes from a disordered configuration into the body-centered cubic configuration. By contrast, upon sufficiently fast non-equilibrium cooling (and not just in the limit of a maximally fast quench), the Voronoi liquid adopts similar states as the effectively hyperuniform inherent structures identified by Klatt et al. and prevents the ordering transition into a body-centered cubic ordered structure. This result is in line with the geometric intuition that the geometric Lloyd's algorithm corresponds to a type of fast quench.
CRIS-Team WoS Importer:2021-01-15

Mean-intercept anisotropy analysis of porous media. I. Analytic formulae for anisotropic Boolean models - Klatt, Michael A.; Schroder-Turk, Gerd E.; Mecke, Klaus (Medical Physics, 2017)
Purpose Structure-property relations, which relate the shape of the microstructure to physical properties such as transport or mechanical properties, need sensitive measures of structure. What are suitable fabric tensors that quantify the shape of anisotropic heterogeneous materials? The mean intercept length is among the most commonly used characteristics of anisotropy in porous media, for example, of trabecular bone in medical physics. Methods We analyze the orientation-biased Boolean model, a versatile stochastic model that represents microstructures as overlapping grains with an orientation bias towards a preferred direction. This model is an extension of the isotropic Boolean model, which has been shown to truthfully reproduce multi-functional properties of isotropic porous media. We explain the close relationship between the concept of intersections with test lines to the elaborate mathematical theory of queues, and how explicit results from the latter can be directly applied to characterize microstructures. Results In this series of two papers, we provide analytic formulas for the anisotropic Boolean model and demonstrate often overlooked conceptual shortcomings of this approach. Queuing theory is used to derive simple and illustrative formulas for the mean intercept length. It separates into an intensity-dependent and an orientation-dependent factor. The global average of the mean intercept length can be expressed by local characteristics of a single grain alone. Conclusions We thus identify which shape information about the random process the mean intercept length contains. The connection between global and local quantities helps to interpret observations and provides insights into the possibilities and limitations of the analysis. In the second paper of this series, we discuss, based on the findings in this paper, short-comings of the mean intercept analysis for (bone-)microstructure characterization. We will suggest alternative and better defined sensitive anisotropy measures from integral geometry.
EAM Import::2019-03-12

Mean-intercept anisotropy analysis of porous media. II. Conceptual shortcomings of the MIL tensor definition and Minkowski tensors as an alternative - Klatt, Michael A.; Schroder-Turk, Gerd E.; Mecke, Klaus (Medical Physics, 2017)
Purpose Structure-property relations, which relate the shape of the microstructure to physical properties such as transport or mechanical properties, need sensitive measures of structure. What are suitable fabric tensors to quantify the shape of anisotropic heterogeneous materials? The mean intercept length is among the most commonly used characteristics of anisotropy in porous media, e.g., of trabecular bone in medical physics. Yet, in this series of two papers we demonstrate that it has conceptual shortcomings that limit the validity of its results. Methods We test the validity of general assumptions regarding the properties of the mean-intercept length tensor using analytical formulas for the mean-intercept lengths in anisotropic Boolean models (derived in part I of this series), augmented by numerical simulations. We discuss in detail the functional form of the mean intercept length as a function of the test line orientations. Results As the most prominent result, we find that, at least for the example of overlapping grains modeling porous media, the polar plot of the mean intercept length is in general not an ellipse and hence not represented by a second-rank tensor. This is in stark contrast to the common understanding that for a large collection of grains the mean intercept length figure averages to an ellipse. The standard mean intercept length tensor defined by a least-square fit of an ellipse is based on a model mismatch, which causes an intrinsic lack of accuracy. Conclusions Our analysis reveals several shortcomings of the mean intercept length tensor analysis that pose conceptual problems and limitations on the information content of this commonly used analysis method. We suggest the Minkowski tensors from integral geometry as alternative sensitive measures of anisotropy. The Minkowski tensors allow for a robust, comprehensive, and systematic approach to quantify various aspects of structural anisotropy. We show the Minkowski tensors to be more sensitive, in the sense, that they can quantify the remnant anisotropy of structures not captured by the mean intercept length analysis. If applied to porous tissue and microstructures, this improved structure characterization can yield new insights into the relationships between geometry and material properties.
EAM Import::2019-03-12

Minimal surfaces in nuclear pasta with the time-dependent hartree-fock approach - Schuetrumpf, Bastian; Klatt, Michael; Iida, K.; Schröder-Turk, Gerd; Maruhn, J. A.; Mecke, Klaus; Reinhard, Paul-Gerhard (Proceedings of Science, 2014)
In continuation to the studies of the whole variety of pasta shapes in [1], we present here calculations performed with the Hartree-Fock and time-dependent Hartree- Fock method concerning the mid-density range of pasta shapes: The slab-like, connected rod-like (p-surface) and the gyroidal shapes. On the one hand we present simulations of the dynamic formation of these shapes at finite temperature. On the other hand we calculate the binding energies of these shapes for varying simulation box lengths and mean densities. All of these shapes are found to be at least metastable. The slab shape has a slightly lower energy because of the lack of curvature, but among these three configurations the gyroidal shape is metastable for the widest range in mean density.
CRIS-Team Scopus Importer:2023-07-24

Minkowski tensor density formulas for Boolean models - Hoerrmann, Julia; Hug, Daniel; Klatt, Michael; Mecke, Klaus (Advances in Applied Mathematics, 2014)
A stationary Boolean model is the union set of random compact particles which are attached to the points of a stationary Poisson point process. For a stationary Boolean model with convex grains we consider a recently developed collection of shape descriptors, the so called Minkowski tensors. By combining spatial and probabilistic averaging we define Minkowski tensor densities of a Boolean model. These densities are global characteristics of the union set which can be estimated from observations. In contrast local characteristics like the mean Minkowski tensor of a single random particle cannot be observed directly, since the particles overlap. We relate the global to the local properties by density formulas for the Minkowski tensors. These density formulas generalize the well known formulas for intrinsic volume densities and are obtained by applying results from translative integral geometry. Our results support the idea that the degree of anisotropy of a Boolean model may be expressed in terms of the Minkowski tensor densities. Furthermore we observe that for smooth grains the mean curvature radius function of a particle can be reconstructed. from the Minkowski tensor densities. In a simulation study we numerically determine Minkowski tensor densities for nonisotropic Boolean models based on ellipses and on rectangles in two dimensions and find excellent agreement with the derived analytic density formulas. The tensor densities can be used to characterize the orientational distribution of the grains and to estimate model parameters for non-isotropic distributions. In particular, the numerically determined values for the density of the Euler characteristic allow the estimation of certain mixed functionals of the grains. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Stochastic geometry; Boolean model; Stationarity; Anisotropy; Minkowski tensors; Poisson process; Translative integral geometry

Minkowski Tensor Shape Analysis of Cellular, Granular and Porous Structures - Peukert, Wolfgang; Schröder-Turk, Gerd; Mickel, Walter; Kapfer, Sebastian; Klatt, Michael; Schaller, Fabian; Hoffmann, Matthias; Kleppmann, Nicola; Inayat, Amer; Armstrong, Patrick; Hug, Daniel; Reichelsdorfer, Martin; et al. (Advanced Materials, 2011)
Predicting physical properties of materials with spatially complex structures is one of the most challenging problems in material science. One key to a better understanding of such materials is the geometric characterization of their spatial structure. Minkowski tensors are tensorial shape indices that allow quantitative characterization of the anisotropy of complex materials and are particularly well suited for developing structure-property relationships for tensor-valued or orientation-dependent physical properties. They are fundamental shape indices, in some sense being the simplest generalization of the concepts of volume, surface and integral curvatures to tensor-valued quantities. Minkowski tensors are based on a solid mathematical foundation provided by integral and stochastic geometry, and are endowed with strong robustness and completeness theorems. The versatile definition of Minkowski tensors applies widely to different types of morphologies, including ordered and disordered structures. Fast linear-time algorithms are available for their computation. This article provides a practical overview of the different uses of Minkowski tensors to extract quantitative physically-relevant spatial structure information from experimental and simulated data, both in 2D and 3D. Applications are presented that quantify (a) alignment of co-polymer films by an electric field imaged by surface force microscopy; (b) local cell anisotropy of spherical bead pack models for granular matter and of closed-cell liquid foam models; (c) surface orientation in open-cell solid foams studied by X-ray tomography; and (d) defect densities and locations in molecular dynamics simulations of crystalline coppe
Keywords: geometric; statistic; spatial; anisotropy; shape; morphology; crystal

Morphometric analysis in gamma-ray astronomy using Minkowski functionals Source detection via structure quantification - Göring, Daniel; Klatt, Michael; Stegmann, C.; Mecke, Klaus (Astronomy & Astrophysics, 2013)
Results. We have successfully applied our method to data of the H.E.S.S. experiment. The morphometric analysis presented here is dedicated to detecting faint extended sources.
Keywords: methods: data analysis; methods: statistical; techniques: image processing; gamma rays: diffuse background

Nuclear Pasta at Finite Temperature with the Time-Dependent Hartree-Fock Approach - Schuetrumpf, B.; Klatt, Michael; Iida, K.; Maruhn, J. A.; Mecke, Klaus; Reinhard, Paul-Gerhard (Journal of Physics: Conference Series, 2016)
We present simulations of neutron-rich matter at sub-nuclear densities, like supernova matter. With the time-dependent Hartree-Fock approximation we can study the evolution of the system at temperatures of several MeV employing a full Skyrme interaction in a periodic three-dimensional grid [1]. The initial state consists of α particles randomly distributed in space that have a Maxwell-Boltzmann distribution in momentum space. Adding a neutron background initialized with Fermi distributed plane waves the calculations reflect a reasonable approximation of astrophysical matter. The matter evolves into spherical, rod-like, connected rod-like and slab-like shapes. Further we observe gyroid-like structures, discussed e.g. in [2], which are formed spontaneously choosing a certain value of the simulation box length. The ρ-T-map of pasta shapes is basically consistent with the phase diagrams obtained from QMD calculations [3]. By an improved topological analysis based on Minkowski functionals [4], all observed pasta shapes can be uniquely identified by only two valuations, namely the Euler characteristic and the integral mean curvature. In addition we propose the variance in the cell-density distribution as a measure to distinguish pasta matter from uniform matter.
CRIS-Team Scopus Importer:2023-07-24

Time-dependent Hartree-Fock approach to nuclear pasta at finite temperature - Schuetrumpf, B.; Klatt, Michael; Iida, K.; Maruhn, J. A.; Mecke, Klaus; Reinhard, Paul-Gerhard (Journal of Physics: Conference Series, 2013)
We present simulations of neutron-rich matter at subnuclear densities, like supernova matter, with the time-dependent Hartree-Fock approximation at temperatures of several MeV. The initial state consists of α particles randomly distributed in space that have a Maxwell-Boltzmann distribution in momentum space. Adding a neutron background initialized with Fermi distributed plane waves the calculations reflect a reasonable approximation of astrophysical matter. This matter evolves into spherical, rod-like, and slab-like shapes and mixtures thereof. The simulations employ a full Skyrme interaction in a periodic three-dimensional grid. By an improved morphological analysis based on Minkowski functionals, all eight pasta shapes can be uniquely identified by the sign of only two valuations, namely the Euler characteristic and the integral mean curvature.
CRIS-Team Scopus Importer:2023-07-24

Time-dependent Hartree-Fock approach to nuclear "pasta" at finite temperature - Schuetrumpf, Bastian; Klatt, Michael; Iida, K.; Maruhn, J. A.; Mecke, Klaus; Reinhard, Paul-Gerhard (Physical Review C - Nuclear Physics, 2013)
We present simulations of neutron-rich matter at subnuclear densities, like supernova matter, with the time-dependent Hartree-Fock approximation at temperatures of several MeV. The initial state consists of alpha particles randomly distributed in space that have aMaxwell-Boltzmann distribution in momentum space. Adding a neutron background initialized with Fermi distributed plane waves the calculations reflect a reasonable approximation of astrophysical matter. This matter evolves into spherical, rod-like, and slab-like shapes and mixtures thereof. The simulations employ a full Skyrme interaction in a periodic three-dimensional grid. By an improved morphological analysis based on Minkowski functionals, all eight pasta shapes can be uniquely identified by the sign of only two valuations, namely the Euler characteristic and the integral mean curvature. In addition, we propose the variance in the cell density distribution as a measure to distinguish pasta matter from uniform matter.

Tracking down the origin of superbubbles and supergiant shells in the Magellanic Clouds with Minkowski tensor analysis - Collischon, Caroline; Sasaki, Manami; Mecke, Klaus; Points, Sean D.; Klatt, Michael A. (Astronomy & Astrophysics, 2021)
Aims. We develop an automatic bubble-recognition routine based on Minkowski functionals (MF) and tensors (MT) to detect bubble-like interstellar structures in optical emission line images. Methods. Minkowski functionals and MT are powerful mathematical tools for parameterizing the shapes of bodies. Using the papaya2-library, we created maps of the desired MF or MT of structures at a given window size. We used maps of the irreducible MT ψ2, which is sensitive to elongation, to find filamentary regions in Hα, [S II], and [O III] images of the Magellanic Cloud Emission Line Survey. Using the phase of ψ2, we were able to draw lines perpendicular to each filament and thus obtain line-density maps. This allowed us to find the center of a bubble-like structure and to detect structures at different window sizes. Results. The detected bubbles in all bands are spatially correlated to the distribution of massive stars, showing that we indeed detect interstellar bubbles without large spatial bias. Eighteen out of 59 supernova remnants in the Large Magellanic Cloud (LMC) and 13 out of 20 superbubbles are detected in at least one wavelength. The lack of detection is mostly due to surrounding emission that disturbs the detection, a too small size, or the lack of a (circular) counterpart in our emission line images. In line-density maps at larger scales, maxima can be found in regions with high star formation in the past, often inside supergiant shells (SGS). In SGS LMC 2, there is a maximum west of the shell where a collision of large gas clouds is thought to have occurred. In the Small Magellanic Cloud (SMC), bubble detection is impaired by the more complex projected structure of the galaxy. Line maps at large scales show large filaments in the SMC in a north-south direction, especially in the [S II] image. The origin of these filaments is unknown.
CRIS-Team Scopus Importer:2021-09-17
Keywords: ISM: structure; Magellanic Clouds; Methods: data analysis; Methods: statistical